SEBUAH KAJIAN MORFOLOGI GENERATIF DALAM â€œSATUA BALI TALES FROM BALIâ€ - I Gusti Ayu Agung Dian Susanthi (Universitas Warmadewa, 2017)
[Title: A Generative Morphology Study in â€˜Satua Bali Tales from Bali'] The diversity and uniqueness of language in the world is an interesting linguistic phenomenon to be studied. Word formation is one of interesting research object, because every language of course has diversity in word formation which is called as morphology process. The theory used in this paper is a theory that is written by experts in the field of morphology. The theory used is the theory of morphology, namely: the theory of generative morphology by Halle (1973), Aronaff (1976), and Scalise (1984). Some examples of words were found in